Restoring identity: the use of religion as a mechanism to transition between an identity of sexual offending to a non-offending identity - Kewley, Stephanie (Criminology & criminal justice, 2017)
This study examines the unique experience of participants who during their reintegration back into the community, following a conviction for sexual offending, re-engaged with religious and spiritual communities. To explore meaning Interpretative Phenomenological Analysis (IPA) was adopted. Four in-depth interviews of men convicted for sexual crimes were undertaken and analysed. Findings indicate that through religious affiliation participants were: exposed to new prosocial networks; provided opportunities to seek forgiveness; felt a sense of belonging and affiliation; and were psychologically comforted. However, the study also found that the process of identity transition from ‘offender’ to ‘non-offender’ was not seamless or straightforward for those with an innate sexual deviancy towards children, caution is therefore advised.